FLEXIBILITY IN WUSHU PRACTITIONERS: A COMPARISON BETWEEN STATIC METHOD AND METHOD OF FACILITATION NEURO-PRÓPRIOCEPTIVO (Fiep Bulletin - online, 2014)
The present study it presents as original article where the effect of two distinct types of training for flexibility, the static method and the method of proprioceptivy neuro facilitation had been compared , the PNF. For such a group of practitioners of Wushu, (the Kung fu in its Olímpica modality) if submitted to the mensuração of the degree of freedom to articulate of both the sides of the lame person-femoral. This measure was registered in angles by means of one goniômetro. After this procedure the individuals had been submitted to the training for one period of time of 12 (twelve) weeks, where the inferior member (MMII) left was submitted to the training for PNF, while MMII the right to the static training. After the 12 (twelve) weeks of training the data had been compared by test T of student, where met a trained superior result for the MMII with method PNF, P= 0,05 (P=0.039) * Significant to the 5% level. Such difference corroborates with diverse research, demonstrating the efficiency of method PNF.
Keywords: Flexibility; allonge; kung fu